FENOMENA WAKIL PEREMPUAN (Di Dewan Perwakilan Rakyat Daerah Kabupaten Garut Periode 2019-2024) - Sholihah, Lilis; Al Farisi, Naufal Ashiil (Fakultas Politik Pemerintahan, 2020)
Deputy garut district council members of the period but only the 2019-2024 is 50 and 9 members legislative women or only 18 % woman to members of the legislature has yet to reach hope 30 % representation of women in garut district council 2019-2024 period. This show representation of women in parliament is still low. While, the act of political parties and election gave opportunities for women to participate in politics and into. legislative institutions. Research conducted has the find out how women are represented in the Regional House of Representatives of Garut in the period 2019-2024 and the inhibiting factors that influence and the efforts made to increase women's representation in the Regional Representative Council of Garut. The theory used is electoral representation theory according to Piktin with four dimensions, namely representative, represented, the substance of representation and context. The method used in the research is a qualitative research method by describing descriptive data and inductive approaches. Supporting data collection methods in research through observation, interviews, and documentation. Data analysis technique used is by reduction of data, display data, and reflecting g conclusion. The research results showed that the representation of women in the the Regional House of Representatives of Garut in the period 2019-2024 was still low. This is caused by internal factors, namely the confidence of women, social relations, double burden and political costs and external factors, namely patriarchal culture and political constraints. In this research we initialize to the government and political parties to do sosialisai the importance of of the representation of women in legislative and suggesting prospective members legoslatif women for developed a good relationship with the community, accommodated and expectations of women in parliament this with to be demonstrated by birth to legal products, programs and policies that are pro against women and as well as improvement system regeneration women. Keywords: Representation of women, regional house of representatives.